KEGIATAN BELAJAR SISWA BERPRESTASI DI SMA PLUS BINA BANGSA KOTA PEKANBARU - Said Achyar Ramadhan; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This thesis is proposed to qualify for a Bachelor of Sociology degree.With the title"Student Learning Activities Achieved In Senior High School Plus Bina BangsaPekanbaru City". The problem discussed in this thesis is how the student learningactivity achievement in Senior High School Plus Bina Pekanbaru city and whatare the activities that support the success of student learning outside schoolhours. Subjects in this study were 7 people. The sampling technique used in thisresearch is purposive sampling technique that is the determination of the sampleaccording to the criteria and the purpose of the research.The method used isqualitative research method because this method explain every problem aboutthis title descriptively. Data filtering instruments used are observations,questionnaires, and documents. The theory used is the theory of motivation,socialization theory and social group theory.The results of general researchconducted then the authors can say that student learning activities achievement inschools more for positive activities that support the learning process and also themechanism of learning in high school Plus Bina Bangsa Pekanbaru can be saidquite well, this is in because the existence of supporting components such asstaffing, curriculum, facilities and infrastructure as well as learners who workand participate in improving the quality of schools.Keywords: activity, student achievement, school,Pekanbaru